Redesain dan Evaluasi Website Bisa Design Menggunakan Pendekatan Design Thinking - Kristiani, Sepia Putri; Sari, Dian Permata (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
The purpose of this research is to know determine the user's convenience in using Bisa Design services and to determine the level of user comfort in Redesigning the Bisa Design website. This method in this research uses design thinking, which includes: empathize, define, ideate, prototype, and test, by collecting data by questionnaire questions given to Bisa Design users, the data is analyzed for obtained the level of the effectiveness and efficiency. The results of this research is different of user’s comfort to uses website Bisa Design. The fact is by evaluation data or user tests, there is a tendency to apply positively for the types of questionnaire questions given.